METRIC DIMENSION OF GRAPH CIRCULANT Cn(1,2,3,4) - (NIM : 90113007), HALIDIN
Let G = (V,E) be a graph with non empty vertex set V (G) and edge set E(G). The distance between two distinct vertices u and v of G denoted by d(u,v) is the length of the shortest path between them in G. For each u ∈ V (G) the representation of u with respect to W is r(u|W) = (d(u,w1),d(u,w2),...,d(u,wk)). The set W called resolving set of G r(u|W) 6= r(v|W), if for every distinct vertices u,v ∈ V (G). The metric dimension β(G) of G is the minimum cardinality of resolving set for G. In this thesis, we determine the metric dimension of circulant graph Cn(1,2,3,4) for n ≥ 10.